The Role of Bhabinkamtibmas through the Healthy Village Program in Preventing the Spread of Covid-19 in the West Lombok Police Area - Alfiyan Ali (Advances in Police Science Research Journal, 2021)
The COVID-19 pandemic has had an impact in various fields and all levels of society, especially in Indonesia. Facing the pandemic, effective prevention efforts are needed so that they can be resolved as early as possible. The right role in preventing the pandemic in the community is Bhabinkamtibmas, with guidance and counseling efforts, the opportunity for the spread of COVID-19 can be minimized through public awareness. The purpose of this paper is to find out the description of the Healthy Village in the West Lombok Police area, the role of Bhabinkmatibmas through the Healthy Village program in preventing the spread of COVID-19 and analyze the factors that influence it. The analytical knife in this research is the Bhabinkamtibmas Concept, the Police Promoter Concept, Management Theory, Cognitive Theory, Role Theory, and Community Participation Theory. The approach that the researcher uses is a qualitative approach with field research methods, which are then collected through several observations, interviews and document studies. The analysis that researchers use next is to reduce data, perform data presentations and make final conclusions. The results showed that the spread of COVID-19 in the West Lombok region was caused by a lack of care and public trust in COVID-19, an unclean surrounding environment, and people's habits of not paying attention to health. So that it has an impact in the fields of health, socioeconomic, education, and security. These things are caused by the negligence and lack of care of the community. The role of Bhabinkamtibmas through the Healthy Village Program is very appropriate in preventing the spread of COVID-19 in the West Lombok Police area. Which is done by coordinating with the local community, Regional Government, Stake Holders by taking actions and appeals with local residents to prevent the spread of COVID-19 by creating their own health protocols in each village or village. The factors that affect the implementation of the Bhabinkamtibmas role are factors that hinder the implementation of the Healthy Village Program which stems from the absence of special budget support for the implementation of the Healthy Village Program, the existence of Bhabinkamtibmas who is responsible for two villages and cultural factors from the community itself. While the supporting factors come from the availability of infrastructure, enthusiasm, expertise, and knowledge of Babinkamtibmas carrying out its role in the Healthy Village Program, the Role of Leaders and community support.